Strategic Management and Social Responsibility Practices of Lending Institutions - Eroy – Tortola, Domely (JPAIR Multidisciplinary Research, 2019)
This study aimed to determine the strategic management and social responsibility practices of lending institutions in Zamboanga del Norte during the year 2018. The descriptive method of research was used with 372 respondents. Frequency counts, percentages, and Pearson Product Moment Correlation (r) were used. Results revealed that the majority of lending institutions were in operation for three years and below. The lending institutions often did strategic management in terms of strategic analysis, strategic decision-making, strategy formulation, strategy implementation, and strategic control. Economic, legal, ethical, and philanthropic responsibilities were often manifested by the lending institutions involved in the study. A significant relationship was noted between strategic management and social responsibility practices. It is recommended that most of the lending industries need to monitor and review the strategic management practiced by their employees. Further, lending institutions are a neophyte in the service and not very familiar with how they play the field of competition; they should assess the competition and potential threats that can affect operation in the market. The top management needs to monitor and review the strategic management practiced by its employees. Further, lending institutions are enjoined to sustain or improve their social responsibility with regards to philanthropic responsibility as this would create a long-lasting impression better image towards their stakeholders.